1999
DOI: 10.1128/aem.65.9.4077-4084.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Some of the Major Groups of Bacteria in Efficient and Nonefficient Biological Phosphorus Removal Activated Sludge Systems

Abstract: To investigate the bacteria that are important to phosphorus (P) removal in activated sludge, microbial populations were analyzed during the operation of a laboratory-scale reactor with various P removal performances. The bacterial population structure, analyzed by fluorescence in situ hybridization (FISH) with oligonucleotides probes complementary to regions of the 16S and 23S rRNAs, was associated with the P removal performance of the reactor. At one stage of the reactor operation, chemical characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 207 publications
(97 citation statements)
references
References 44 publications
2
91
0
2
Order By: Relevance
“…As a consequence, the system became robust giving it greater resistance to occasional perturbations, more stable leading to nearly constant phosphorus removal, and improved its EBPR capacity, relative to the period with pH control. An improvement in reactor stability and phosphorus removal efficiency was reported by Bond et al (1999a) when they removed pH control in the anaerobic period. However, in that study, the aerobic pH was controlled at 7.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…As a consequence, the system became robust giving it greater resistance to occasional perturbations, more stable leading to nearly constant phosphorus removal, and improved its EBPR capacity, relative to the period with pH control. An improvement in reactor stability and phosphorus removal efficiency was reported by Bond et al (1999a) when they removed pH control in the anaerobic period. However, in that study, the aerobic pH was controlled at 7.…”
Section: Discussionmentioning
confidence: 96%
“…This difference could be caused by a different microbial community development under the different pH operating conditions. Bond et al (1999a) reported a sludge with a GAO phenotype and dominated by betaproteobacteria from subgroups other than 1 and 2 when operation was with complete pH control at 7. Subsequently, when the pH was controlled at 7 only during the aerobic period, the sludge demonstrated a PAO phenotype and the microbial community was more diverse but composed of 55% betaproteobacteria from subgroup 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations